Biological features and quality comprehensive analysis of twelve germplasm resources of the genus Allium from Tibet - Wang, Huaifeng; Yang, Haixing; Yu, Xuena; Xie, Yongdong; Bai, Yu; Dai, Qiya; Liang, Le; Tang, Wen; Yong, Mao; Wang, Luzhou; Huang, Zhi; Sun, Bo; et al. (Frontiers in Plant Science, 2024)
Allium is important vegetables and seasonings in China, Tibet is rich in unique resources of the genus Allium, but lacks development and utilization. We compared the biological features and comprehensively evaluating the quality of twelve germplasm resources of the genus Allium collected from Tibet. The results revealed that nine germplasm resources were bolting and bloom normally except for SC015, SC019, and SC048, all twelve germplasm resources were able to vegetative growth. The individual differences in moisture, soluble sugar, and protein content among the twelve germplasm resources were relatively small, with pyruvic acid content ranging from 0.11 to 1.12 mg/g and a large variation coefficient. A total of 8 categories and 97 volatile compounds were detected in twelve germplasm resources, the majority possessed the highest proportions of aldehydes and organosulfur compounds, but there were certain differences between the different Allium species. Additionally, 11 to 16 types of free amino acids were present in all germplasm resources, proline exhibited the highest content. The total content of essential and non-essential amino acids in SC009 was the highest. Carbon (C) accounted for the largest proportion of all elements, and the contents of other mineral elements varied greatly among the different plants. In conclusion, combined with biological performance and comprehensive evaluation of quality, SC009 is the excellent germplasm resource suitable for growth and capable of reproduction with good quality. These results improved the exploitation and utilization of the genus Allium in Tibet, as well as provided germplasm resources for high-quality breeding of the genus Allium.